CHYDENANTHUS MIERS (LECYTHIDACEAE): A CORRECTION - Kartawinata, Kuswata (Research Center for Biology, 1984)
In my article on the genus ChydenmUhus Miers in Reinwardtia 10 (1) : 28, 1982, I stated that